2011
DOI: 10.3892/or.2011.1331
|View full text |Cite
|
Sign up to set email alerts
|

All reovirus subtypes show oncolytic potential in primary cells of human high-grade glioma

Abstract: Abstract. Reoviridae are non-human pathogenic viruses. The family of reoviridae consists of 4 different subtypes. Many studies have proven that the Dearing subtype 3 has oncolytic potential. This potential is related to the RAS protein expression in tumour cells. The aim of this study, was to investigate whether all reovirus subtypes have oncolytic potential and whether there are differences in their efficacy, in particular for high-grade glioma. To evaluate the oncolytic potential, we performed an in vitro he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Reovirus type 3 Dearing, isolate Cashdollar (T3D C ) is currently being used in clinical studies and is mainly studied for its oncolytic properties . Recently, all of the reovirus subtypes have been shown to have oncolytic potential . Reovirus strains differ in both replication and pathogenic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Reovirus type 3 Dearing, isolate Cashdollar (T3D C ) is currently being used in clinical studies and is mainly studied for its oncolytic properties . Recently, all of the reovirus subtypes have been shown to have oncolytic potential . Reovirus strains differ in both replication and pathogenic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Neurotoxicity initially observed in immunocompromised animals was absent in immune-competent rodent glioma models, and non-human primates injected intracranially with GMP-grade reovirus showed no neurotoxicity or measurable adverse effect 74 , paving the way for two clinical trials 75 . A recent study showed reovirus oncolytic effect against glioma generalized among several reovirus strains 76 , opening the possibility for potentially repetitive application of serotype-switched reoviruses.…”
Section: Oncolytic Virus Candidates For High Grade Gliomamentioning
confidence: 99%
“…While intracranial reovirus administration was neurotoxic in severely immunodeficient animals (77), it was nontoxic in immunocompetent rodents and nonhuman primates (78). Recently, all four serotypes of reovirus have been shown to have oncolytic activity in glioma cell lines, as well as in GSCs (79, 80). …”
Section: Oncolytic Viruses In Clinical Trial For Gliomamentioning
confidence: 99%